Where Do You Stand? Discussions That Promote Democratic Citizenship and Engage Multiple Intelligences. Issue 2 (April 2019) - Arnold, Bryan P.
Teachers often desire meaningful classroom discussions, but frequently shy away from introducing controversial topics. An instructional activity "Where Do You Stand?" was developed and used regularly with the goal of engaging students in discussion around politicized and divisive issues. Over 3 years of use in a secondary social studies classroom, benefits of fostering democratic citizenship and engaging a range of multiple intelligences were observed. Beyond social studies, there are viable adaptations for use across content areas, in multiple forms, and recommendations to maximize the observed benefits. "Where Do You Stand?" offers teachers an opportunity to invite learners into critically important conversations.